A Series of Panic Disorder Cases Treated with Detached Mindfulness - Atmaca, Murad; Tabara, Muhammed Fatih; Gurok, Mehmet Gurkan (Aves, 2024)
Background: Studies evaluating the efficacy of detached mindfulness (DM) as a stand- alone intervention for patients with panic disorder are lacking in the literature. In this con- text, the aim of this open study was to evaluate the efficacy of DM in patients with panic disorder. Methods: The study was conducted in 11 patients (7 females and 4 males). The DM ther- apy process was applied to the patients. The clinical course was followed using the Panic Disorder Severity Scale (PDSS), the Beck Anxiety Inventory (BAI), and the Beck Depression Inventory (BDI). Results: Patients' attendance at therapy and completion of DM homework were found to be quite good. Patients' PDSS scores decreased significantly at the end of treatment com- pared to baseline. A similar change was seen in the BAI and BDI scores. Conclusion: In conclusion, it can be stated that DM is an effective, easily applicable, and highly therapeutic method for the treatment of patients with panic disorder. However, the present study needs to be supported by future studies with larger samples.
Keywords: Panic disorder; mindfulness; metacognition; psychotherapy